Creativity and Innovation Skills in Child-Friendly Mathematics Learning in Elementary School - Meggy Novitasari; Bambang Sumardjoko; Erni Suharini; Mintarsih Arbarini (Universitas Negeri Semarang, 2021)
The purpose of the research is to describe creativity and innovation skills in: 1) introduction, 2) contents, and 3) closing of child-friendly mathematics learning in elementary schools. This type of qualitative research is ethnography. The research was conducted at Muhammadiyah 16 Surakarta Elementary School in 2020/2021. Data collection techniques with participatory observation, indepth interviews, and document analysis. Research data validation is done by triangulating sources and methods. Analysis of research data was performed inductive. The results of the study, creativity and innovation skills in child-friendly mathematics learning, was conducted in the introduction, contents, and closing activities. Creativity and innovation skills in the first indicator, students can be competent in both cognitive, affective and psychomotor aspects. Creativity and innovation skills in the second indicator, familiarize and cultivate students to be literate. Creativity and innovation skills in the third indicator, improve teacher performance. Creativity and innovation skills in child-friendly mathematics learning are shown in an attitude of anti-violence and bullying, mutual respect, creative thinking, discipline, fun learning, friendship, differences of opinion both at school and at home, caring for the environment, and protecting the small and exclueded.